Effectiveness of the Management of Drug-drug Interactions in Inpatients through the Drug Interaction Warning System and Clinical Pharmacy Activity at Lao Cai General Hospital - Thi Thuy An, Nguyen; Van Thinh, Pham; Thanh Hai, Nguyen; Xuan Bach, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 37 No 2, 2021)
In prescribing practice for inpatients, quickly detecting pairs of drug-drug interactions (DDIs) and providing prompt management when prescribing is of utmost importance in ensuring safe and rational use of drugs. Subjects and research methods: All prescriptions with DDIs warnings for inpatients from 1/1/2021 to 31/3/2021 on the residue reporting system at Lao Cai General Hospital. The research is designed as a cohort study. Results: In 3 months of implementing DDIs surveillance on the system of reporting, there were 214 times of DDIs occurring in 157 inpatients, of which 2 were contraindicated DDIs and 212 severe DDIs. Patients with DDIs have the mean age and number of diseases, respectively: 63.2 ± 17.5 (years) and 4.3 ± 1.87 (diseases). 2 patients with contraindicated DDIs of a clarithromycin-lovastatin pair received direct feedback from pharmacists to agree to cancel the prescription; Patients with severe DDIs are also discussed by pharmacists to agree on the most appropriate management for each patient, such as 77.83% of clinical supervision; 7.08% of replacement medicine; 2.83% of following up more tests; 1.89% of stopping using drugs. Conclusion: The DDIs warning system and clinical pharmacy activity have managed all pairs of DDIs that often occur on inpatients at Lao Cai General Hospital. Keywords Drug interaction warning system, clinical pharmacy activities, Lao Cai General Hospital. References